The Preservation of Femininity in A. K. Summers’ Pregnant Butch - Ibrahim, Laila Nabilahtuzzahro; Pasopati, Rommel Utungga (CV. Tripe Konsultan, 2024)
This study examines the depiction of femininity in the graphic novel Pregnant Butch by A. K. Summers. The novel follows the story of Teek, who is experiencing pregnancy as a butch lesbian for the first time. This article investigates Teek’s sustaining femininity throughout her pregnancy journey as a butch. A butch itself is a gender expression that holds a masculine role in lesbian relationships. The researchers took the data of this analysis is taken by reading the graphic novels thoroughly, approaching the analysis from Teek's perspective, compiling a list of dialogues and interactions, and categorizing the collected data into specific themes. Using a qualitative method, the researchers in this analysis underline the uniqueness between masculinity and femininity illustrated in the graphic novel. In conclusion, Teek's experience of femininity during pregnancy enriches her butch identity, emphasizing her ability to balance both masculine and feminine aspects of herself. The study highlights the significance of feminine elements in Teek's unwavering expression of femininity.